Pembelajaran dengan Aplikasi Canva pada Materi Perkembangan Pesantren dan Peranannya dalam Dakwah Islam di Indonesia - Thoyibah, Firda Amalia; Hajizah, Hajizah (ISLAMIKA, 2025)
This study aims to examine the design of learning videos using the Canva application on the material of the development of Islamic boarding schools and their role in Islamic propagation in Indonesia. The instrument used in testing the feasibility of learning video design is to use a validation sheet questionnaire by material experts and media experts. Feasibility is seen from the results of validation by material experts which include the feasibility of material content, question content, and language. While the feasibility of the results of media expert validation includes the feasibility of cover design and video content design. The method used in this research is Research and Development (R&D) with the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages. However, this research is limited to the Develop stage only. The research process began with a needs analysis at MTs Hidayatul Muhajirin Palangka Raya, followed by the design and development of learning videos that were tested for validity by material experts and media experts. The validation results showed that the learning video design obtained 85% results from material experts who were included in the very feasible category, and 77% from media experts who were included in the feasible category. Thus, the learning video design produced can be applied effectively in schools with minimal use of learning media.